Analysis of Financial Performance Before and During the Covid-19 Pandemic Era at PT. Bank Rakyat Indonesia (BRI) TBK - Ranti Nurdiansari; Heliani; Erma Susilawati; Anis Sriwahyuni; Elin Paulina (Nusantara Science and Technology Proceedings, 2020)
This study aims to analyze the financial performance at PT Bank Rakyat Indonesia Tbk. and so that the difference in financial performance before and during the Covid-19 pandemic are known and also to determine the effect of the Covid-19 pandemic on financial performance at PT. Bank Rakyat Indonesia (Persero) Tbk. So that this research can be used by company management to evaluate the performance of PT. Bank Rakyat Indonesia Tbk. so that it better and also as a consideration for investors who want to invest. The financial statements used for analysis are the second quarterly financial reports that have been published on the Indonesian stock exchange. This study uses financial cash ratio, loan to deposit ratio, primary ratio, capital adequacy ratio, return on equity, and return on asset. The results of this study show that the level of cash ratio, loan to deposit ratio, primary ratio, capital adequacy ratio, return on asset, and return on equity has decreased in 2020.